Decoding Consumer Buying Behavior: Key Factors That Drive Purchase Decisions - Mudassir Sajjad; Malaika Asif; Corresponding Author:Muhammad Mubashir khan (Al-Qanṭara, 2025)
Consumer buying behavior is a multifaceted process influenced by psychological, social, and economic factors, as well as brand-related constructs such as brand image, brand association, perceived quality, and brand awareness. This study investigates the complex interplay between these constructs and their collective impact on purchase intention and consumer behavior. Employing a quantitative research design, data was gathered from 500 respondents using a structured survey instrument. Statistical analyses, including exploratory factor analysis (EFA) and structural equation modeling (SEM), were conducted to validate the hypothesized relationships. The findings reveal that brand image (β = 0.42, p < 0.001) and brand awareness (β = 0.40, p < 0.001) significantly influence purchase intention, with perceived quality (β = 0.38, p < 0.001) and brand association (β = 0.35, p < 0.01) also playing crucial roles. Furthermore, purchase intention mediates the relationship between brand constructs and consumer buying behavior, underscoring its pivotal role in translating brand equity into tangible consumer actions. The demographic analysis highlights the prevalence of younger, educated, and financially stable consumers as key decision-makers, emphasizing the importance of tailoring marketing strategies to this segment. The study employs a robust methodological framework to ensure the reliability and validity of its findings. The survey instrument demonstrated high internal consistency, with Cronbach’s alpha values exceeding 0.80 for all constructs. Model fit indices further validated the proposed relationships, with CFI = 0.95 and RMSEA = 0.05 indicating excellent fit. These results affirm the critical importance of brand management in influencing consumer behavior and provide actionable insights for businesses seeking to enhance their market positioning. The implications of these findings are significant for both theory and practice. From a theoretical perspective, the study extends existing frameworks, such as the Theory of Planned Behavior and the Stimulus-Organism-Response model, by integrating brand-specific constructs. From a practical standpoint, the results offer valuable recommendations for businesses to optimize their branding strategies, foster customer loyalty, and drive sustainable growth. For example, companies should invest in enhancing brand image through targeted marketing campaigns, improving perceived quality via product innovation, and increasing brand awareness through digital engagement and social media. In addition to offering managerial insights, this study identifies areas for future research. While the cross-sectional design provides a snapshot of consumer behavior, longitudinal studies could explore how these relationships evolve over time. Further, the study’s focus on specific industries limits the generalizability of its findings. Future research could expand to different sectors and geographic regions to provide a more comprehensive understanding of consumer behavior in diverse contexts. Investigating emerging factors such as digital transformation, sustainability, and cultural influences could also enrich the literature and provide deeper insights into the evolving consumer landscape. In conclusion, this research underscores the importance of understanding consumer behavior to develop effective branding and marketing strategies. By elucidating the relationships between brand constructs, purchase intention, and consumer behavior, the study provides a roadmap for businesses to enhance their competitive advantage in dynamic and competitive markets. These findings emphasize the need for an integrated approach to brand management, leveraging consumer insights to create meaningful connections, foster loyalty, and drive long-term success.